Where sky meets sea: Integrated aerosol and ocean color retrieval from PACE SPEXone multi-angle polarimetry - Meng Gao; Kamal Aryal; Peng-Wang Zhai; Kirk Knobelspiesse; Bryan Franz; Brian Cairns; Ivona Cetinić; Guangliang Fu; Otto Hasekamp; Amir Ibrahim; Andrew M. Sayer; P. Jeremy Werdell (Remote Sensing of Environment, 2026)

Mid-Infrared spectroscopy for soil organic carbon estimation. Part I: Global review and meta-analysis - Tong Li; Anquan Xia; Ram C. Dalal; Sean Manning; Deeksha Beniwal; Zhihong Xu; Rajiv Pandey; Lizhen Cui; Songchao Chen; Peng Fu; Yushu Xia; Jinran Wu; et al. (Soil and Tillage Research, 2026)

Mid-infrared spectroscopy for soil organic carbon estimation. Part II: Evaluating preprocessing at global and national scales - Tong Li; Deeksha Beniwal; Ram C. Dalal; Sean Manning; Peng Fu; Anquan Xia; Jinran Wu; Qingyang Liu; Vilim Filipović; Georgios Tsiminis; Yash P. Dang (Soil and Tillage Research, 2026)

Zircon geochronology of the Gordonbrook Serpentinite: A fragment of mantle wedge within the New England Orogen, eastern Australia - George G.F. Murray; Solomon Buckman; Allen P. Nutman; Wanchese M. Saktura; Jonathan C. Aitchison; Vickie C. Bennett; Zhen Yan; Changlei Fu (Lithos, 2026)

Consumer preferences for simultaneous presentation of nutrition and environmental labelling: Evidence from a discrete choice experiment at UK scale - Rao Fu; Shan Jin; Francisco Areal; Paul Brereton; Jayne V. Woodside; Jelena Vlajic; Beatrice Smyth; Anne P. Nugent; David Livingstone; George Hutchinson; Eva-Leanne Thomas; Leona Lindberg; et al. (Food Quality and Preference, 2026)

Role of oceanic biogenic emissions of dimethyl sulfide in air sulfur chemistry along the southeastern Pacific Chilean coast - Ernesto Pino-Cortés; Mariela Martínez-Pastén; Samuel Carrasco; Katherine Gómez; Joshua S. Fu; Fernando González Taboada; Alfonso Saiz-Lopez; Rafael P. Fernandez; Jonathan Acosta; Golam Sarwar; Juan Höfer (Atmospheric Pollution Research, 2026)

Immune divergence in rainbow trout lines selectively bred for F. psychrophilum resistance or susceptibility revealed by challenge with Weissella tructae - Gregory D. Wiens; Christopher C. Chadwick; Keira Osbourn; Qin Fu; Ross M. Reid; Travis Moreland; Timothy J. Welch; Timothy D. Leeds; David P. Marancik (Fish & Shellfish Immunology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Brachiopods and associated skeletal taxa from the early Cambrian of southeastern Shaanxi, South China - Mei Luo; Timothy P. Topper; Guoxiang Li; Baopeng Song; Zhao Wang; Caibin Zhang; Jingliang Zhao; Peiyao Wang; Rao Fu; Fan Liu; Zhifei Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Drought as a risk amplifier: The intensifying regime of compound dry-hot events in China - Pengcheng Xu; Dong Wang; Yuankun Wang; Vijay P. Singh; Jianchun Qiu; Xiaolei Fu (Atmospheric Research, 2026)

Medicinal seahorses (Hippocampus spp.) for Alzheimer’s disease within species conservation framework: an integrated review of ethnopharmacology, bioactivity, bibliometrics, and network pharmacology - Peng Song; Mengyu Wang; Tao Liu; Zhuoqing Zhang; Xia Ren; Yao Liu; Jerome P. L. Ng; Vincent Kam Wai Wong; Betty Yuen Kwan Law; Xianjun Fu; Liqun Qu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Non‐Correlated Variation of Leaf and Fine Root Traits in Subtropical Forest Plants - Yuzhi Zhu; Meng Li; Junyong Zheng; Yongqiang Wang; Yanghang Ren; Han Zhang; Zeyu Feng; Sandy P. Harrison; I. Colin Prentice; Yue Zhang; Lewei Jin; Shuang Sun; et al. (Ecology Letters, 2026)
Plants employ multiple strategies to adapt to their growth environment. Characterizing key dimensions in plant trait space is important for understanding functional diversity within ecosystems. Leaf and root functional traits have been studied in the context of resource economics, but whether they covary, and through which mechanisms, is still debated. We investigated this in subtropical forests by sampling root and leaf traits on individuals of co‐existing species in two communities with different resource availability. We found largely non‐correlated variation between leaf and fine root traits both across and within communities, and a clear decoupling between leaf economic spectrum and root economic space, independent of evolutionary history. Our results suggest that leaf‐root trait relationships are shaped by an interplay between microenvironmental heterogeneity that drives decoupling and shared selection pressures promoting covariation. The interplay explains the weak observed coordination and highlights the importance of environmental context in predicting above‐ and below‐ground plant functions.

Quantitative assessment of the reservoir-induced impact on multivariate flood risk via the nonstationary Vine Copula model - Pengcheng Xu; Zhilang Zhang; Dong Wang; Vijay P. Singh; Gengxi Zhang; Xiaolei Fu; Huanyu Yang (Journal of Hydrology, 2026)

Incorporation of D-amino Acids and Ornithines into Tirzepatide by Biosynthesis in E. Coli - Yanli Xu; Yuxin Fu; Oscar P. Kuipers (International Journal of Peptide Research and Therapeutics, 2026)
Purpose Tirzepatide is an effective dual GLP-1 and GIP receptor agonist for type 2 diabetes and obesity but faces challenges with low oral bioavailability and stability. Currently, tirzepatide is produced industrially via solid-phase peptide synthesis (SPSS), allows incorporation of noncanonical residues but limited in scalability for rapid mutant generation and biological delivery strategies. This study aimed to develop a microbial biosynthetic platform for tirzepatide production to enable efficient mutant library construction and stability optimization. Methods A ribosomal synthesis and post-translational modification (RiPP)-based microbial expression system was engineered for tirzepatide biosynthesis. Ornithine residues were introduced at positions 2 and 13 through enzymatic arginine conversion. Co-expression of the RiPP-associated enzyme OspD enabled incorporation D amino acids. Structural characterization was conducted using circular dichroism spectroscopy, and peptide stability was evaluated in human serum. Results The engineered system successfully produced tirzepatide and its designed mutants. Site-specific ornithine incorporation and D amino acid modifications were achieved. Circular dichroism analysis revealed structural alterations in the modified peptides. Human serum assays demonstrated that the engineered mutants remained stable for at least two days, indicating proteolytic resistance. Conclusion This work establishes a feasible microbial RiPP-based strategy for tirzepatide biosynthesis, providing a foundation for rapid mutant generation, structural optimization, and development of microbial-based peptide delivery systems.

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Metagenomic insights into species shifts and adaptation mechanisms of anammox communities treating incineration leachate - Da Kang; Yikai Zhao; Xinran Zhang; Xianyong Zeng; Xindi Fu; Bingxin Li; Zheng Ge; Liang Zhang; James P. Shapleigh; Yongzhen Peng (Chemical Engineering Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Mineral Association and Microbial Processing Jointly Prolong Carbon Turnover in Coastal Wetlands - Yuan Li; Chuancheng Fu; Peng Ren; Zhaoliang Song; Lingfang Ni; Ting Wang; Changxun Yu; Ji Chen; Laodong Guo; Iain P. Hartley; Ding He; Xiaoguang Ouyang; et al. (Global Change Biology, 2026)
Coastal margins are critical sites for carbon (C) sequestration, yet the mechanisms stabilizing preaged, allochthonous C (externally‐derived biospheric C) in these environments remain poorly understood. Specifically, the interplay between mineral association and microbial processing represents a significant knowledge gap. Here, we investigated C sequestration mechanisms in Chinese mangrove and saltmarsh soils by analyzing topsoils and cores across 36 sites spanning a 20‐degree latitudinal transect. We found that saltmarshes, characterized by high mineral accretion and lower relative autochthonous C accumulation, exhibited significantly longer soil organic C (SOC) turnover times than mangroves (topsoils: ~2200 vs. ~500 years, respectively). This difference corresponded to higher proportions of preaged (~50%) and petrogenic (rock‐derived; ~20%) SOC in saltmarshes. Linear mixed‐effects models (LMM) confirmed that proxies for mineral protection (e.g., Al/Si) and advanced decomposition (lignin oxidation) were robust, positive predictors of turnover time across the latitudinal gradient. Further structural equation modeling (SEM) indicated a depth‐dependent shift in drivers. In surface soils, microbial necromass accumulation was a significant predictor of C turnover (coefficient = 0.36). However, at depth (1 m), the degree of lignin degradation emerged as the primary predictor of multi‐millennial C persistence (coefficient = 0.45). These results suggest a joint regulation mechanism whereby microbial processing transforms organic matter into stable forms that are subsequently protected by minerals. This mechanism effectively sequesters old, allochthonous C, challenging the paradigm that blue C storage is dominated solely by recent biomass and necessitating a reevaluation of coastal C management frameworks.

Intensification of extreme precipitation across the Tibetan Plateau and its climatic drivers over 1982−2020 - Yiming Song; Shiqin Xu; Dennis P. Lettenmaier; Hylke E. Beck; Xiaodong Chen; Zhongbo Yu; Ningpeng Dong; Qian Cao; Xiaolei Fu; Zhe Yang; Yuliang Zhang; Matthew F. McCabe (Global and Planetary Change, 2026)

Apatite cathodoluminescence and trace element geochemistry of Neoarchean and Paleoproterozoic iron oxide-copper-gold (IOCG) deposits of the Carajás domain, Brazil: implications for fluid evolution and metallogenesis - Raphael B. Hunger; Carolina P. N. Moreto; Roberto P. Xavier; Gustavo H. C. de Melo; Lena V. S. Monteiro; Gláucia N. Queiroga; Cristiano de C. Lana; Wang Liao; Xin-Fu Zhao; Poliana I. de F. Toledo (Mineralium Deposita, 2026)

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

Deep learning model for fast, science-based forecasting of fluid migration along faults in geologic carbon storage scenarios - Hyeonseok Lee; Paul E. Kim; Shaowen Mao; Shuojia Fu; Axel P. Indro; Seunghwan Baek; Nate Mitchell; Mohamed Mehana (International Journal of Greenhouse Gas Control, 2025)

Natural and anthropogenic drivers of salinization in the Bohai Rim: Mechanisms and remediation through pine needle amendments - Baijun Shang; Feng Wang; Tong Li; Zhihong Xu; Bernhard Wehr; Yash P. Dang; Rongxiao Che; Lizhen Cui; Jintong Liu; Hui Gao; Shuhui Yu; Tonggang Fu (Journal of Soils and Sediments, 2025)

Coupled modeling of rice growth and quality accumulation facilitates efficient, high-quality and precision water management - Wenhao Dong; Aizheng Yang; Qiang Fu; Vijay P. Singh; Lili Zhangzhong; Pingan Zhang; Xiaofang Wang; Kun Hu; Mo Li (Agricultural Systems, 2025)

Time-Dependent Deformation Model of the Rock Mass Integrating the Effect of Groundwater with Application to Slope Stability - Tengfei Fu; Tao Xu; Michael J. Heap; Shengqi Yang; Susheng Wang; P. L. P. Wasantha; Zhiguo Li (Rock Mechanics and Rock Engineering, 2025)

Investigating Sulfotransferase Mediated Drug Interactions of Ethinylestradiol using a Physiologically Based Pharmacokinetic Model - Harry P. Moore; Kuan-Fu Chen; Aki T. Heikkinen; Sibylle Neuhoff; Udoamaka Ezuruike; Jean Dinh; Iain Gardner; Hannah M. Jones; Felix Stader (The AAPS Journal, 2025)

Revalorization of fish viscera as a sustainable source of proteins, lipids and polysaccharides in the food industry - Sirong Huang; Binbin Yu; Bei Wang; Olugbenga P. Soladoye; Soottawat Benjakul; Yuhao Zhang; Yu Fu (Critical Reviews in Food Science and Nutrition, 2025)

Non-synergistic effect of marginal distribution and dependence structure of extremes triggering the future risk of compound dry-hot events in Yellow River, China - Pengcheng Xu; Tong Zhu; Dong Wang; Yuankun Wang; Vijay P. Singh; Miao Lu; Xiaolei Fu (Stochastic Environmental Research and Risk Assessment, 2025)

Limited Regulation of Canopy Water Use Efficiency by Stomatal Behavior Under Drought Propagation - Feng Li; Qinchuan Xin; Chuixiang Yi; Steven A. Kannenberg; Julia K. Green; Mirco Migliavacca; David J. P. Moore; Armen R. Kemanian; Pierre Gentine; Paul C. Stoy; Fangyue Zhang; Yujiu Xiong; et al. (Global Change Biology, 2025)
Water use efficiency (WUE) is a critical ecosystem function and a key indicator of vegetation responses to drought, yet its temporal trajectories and underlying drivers during drought propagation remain insufficiently understood. Here, we examined the trajectories, interdependencies and drivers of multidimensional WUE metrics and their components (gross primary production (GPP), evapotranspiration, transpiration (T), and canopy conductance (Gc)) using a conceptual drought propagation framework. We found that even though the carbon assimilation efficiency per stomata increases during drought, the canopy‐level WUE (represented by transpiration WUE (TWUE)) declines, indicating that stomatal regulation operates primarily at the leaf level and cannot offset the drought‐induced reduction in WUE at the canopy scale. A stronger dependence on T and TWUE indicates that the water–carbon trade‐off relationship of vegetation more inclines toward water transport than carbon assimilation. Gc fails to prevent the sharp decline in GPP during drought and has limited capacity to suppress T, as reflected by the reduction magnitude and the threshold (the turning point at which a component shifts from a normal to drought‐responsive state). The primary drivers of the water–carbon relationship under drought propagation include vapor pressure deficit and hydraulic traits. Among plant functional types, grasslands show the strongest water–carbon fluxes in response to drought, whereas evergreen broadleaf forests exhibit the weakest response. These findings refine our comprehensive understanding of multidimensional ecosystem functional dynamics under drought propagation and enlighten how the physiological response of vegetation to drought affects the carbon and water cycles.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

Increasing humification and reducing CH4 emission during rice straw fermentation: the role of Streptomyces rochei ZY-2 - B. Fu; B. Gao; J. Zhang; H. Huang; Z. Wei; Q. Wang; P. Qu (International Journal of Environmental Science and Technology, 2025)

Green and efficient fine control of regional irrigation water use coupled with crop growth-carbon emission processes - Mo Li; Lijuan Wang; Vijay P. Singh; Yingshan Chen; Haiyan Li; Tianxiao Li; Zhaoqiang Zhou; Qiang Fu (European Journal of Agronomy, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The EGS Collab project: Outcomes and lessons learned from hydraulic fracture stimulations in crystalline rock at 1.25 and 1.5 km depth - Tim Kneafsey; Pat Dobson; Doug Blankenship; Paul Schwering; Mark White; Joseph P. Morris; Lianjie Huang; Tim Johnson; Jeff Burghardt; Earl Mattson; Ghanashyam Neupane; Chris Strickland; et al. (Geothermics, 2025)

Perspective of explosive cyclones with three shapes of upper-level potential vorticity over the northern Atlantic Ocean - J. Ni; G. Fu; L. J. Chen; P. Y. Li (Climate Dynamics, 2025)

Towards food-derived self-assembling peptide-based hydrogels: Insights into preparation, characterization and mechanism - Chenxiao Zhu; Wei Wu; Olugbenga P. Soladoye; Na Zhang; Yuhao Zhang; Yu Fu (Food Chemistry, 2024)

Toward the high-efficient utilization of poultry blood: Insights into functionality, bioactivity and functional components - Hanyuan Zheng; Shulei Zhao; Yujia Lu; Na Zhang; Olugbenga P. Soladoye; Yuhao Zhang; Yu Fu (Critical Reviews in Food Science and Nutrition, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Correction: Histamine induces the production of matrix metalloproteinase-9 in human astrocytic cultures via H1-receptor subtype - Aarti Patel; Vishnu Vasanthan; Wen Fu; Richard P. Fahlman; David MacTavish; Jack H. Jhamandas (Brain Structure and Function, 2024)

Soil autotrophic-to-heterotrophic-respiration ratio and its controlling factors across several terrestrial biomes: A global synthesis - Chuan Jin; Jinshi Jian; Charles P.-A. Bourque; Tianshan Zha; Licong Dai; Yue Yang; Ruiyu Fu; Qiaoyan Chen; Peng Liu; Xinhao Li; Zifan Guo; Zhongmin Hu (CATENA, 2024)

Cortical and spinal responses to short-term strength training and detraining in young and older adults in rectus femoris muscle - Gonzalo Gomez-Guerrero; Janne Avela; Ilkka Jussila; Esa Pihlajamäki; Fu-Yu Deng; Dawson J. Kidgell; Juha P. Ahtiainen; Simon Walker (European Journal of Applied Physiology, 2024)
Introduction Strength training mitigates the age-related decline in strength and muscle activation but limited evidence exists on specific motor pathway adaptations. Methods Eleven young (22–34 years) and ten older (66–80 years) adults underwent five testing sessions where lumbar-evoked potentials (LEPs) and motor-evoked potentials (MEPs) were measured during 20 and 60% of maximum voluntary contraction (MVC). Ten stimulations, randomly delivered, targeted 25% of maximum compound action potential for LEPs and 120, 140, and 160% of active motor threshold (aMT) for MEPs. The 7-week whole-body resistance training intervention included five exercises, e.g., knee extension (5 sets) and leg press (3 sets), performed twice weekly and was followed by 4 weeks of detraining. Results Young had higher MVC (~ 63 N·m, p = 0.006), 1-RM (~ 50 kg, p = 0.002), and lower aMT (~ 9%, p = 0.030) than older adults at baseline. Young increased 1-RM (+ 18 kg, p < 0.001), skeletal muscle mass (SMM) (+ 0.9 kg, p = 0.009), and LEP amplitude (+ 0.174, p < 0.001) during 20% MVC. Older adults increased MVC (+ 13 N·m, p = 0.014), however, they experienced decreased LEP amplitude (− 0.241, p < 0.001) during 20% MVC and MEP amplitude reductions at 120% (− 0.157, p = 0.034), 140% (− 0.196, p = 0.026), and 160% (− 0.210, p = 0.006) aMT during 60% MVC trials. After detraining, young and older adults decreased 1-RM, while young adults decreased SMM. Conclusion Higher aMT and MEP amplitude in older adults were concomitant with lower baseline strength. Training increased strength in both groups, but divergent modifications in cortico-spinal activity occurred. Results suggest that the primary locus of adaptation occurs at the spinal level.

Mycorrhizal associations relate to stable convergence in plant–microbial competition for nitrogen absorption under high nitrogen conditions - Zhenggang Du; Lingyan Zhou; Madhav P. Thakur; Guiyao Zhou; Yuling Fu; Nan Li; Ruiqiang Liu; Yanghui He; Hongyang Chen; Jie Li; Huimin Zhou; Ming Li; et al. (Global Change Biology, 2024)
Nitrogen (N) immobilization (Nim, including microbial N assimilation) and plant N uptake (PNU) are the two most important pathways of N retention in soils. The ratio of Nim to PNU (hereafter Nim:PNU ratio) generally reflects the degree of N limitation for plant growth in terrestrial ecosystems. However, the key factors driving the pattern of Nim:PNU ratio across global ecosystems remain unclear. Here, using a global data set of 1018 observations from 184 studies, we examined the relative importance of mycorrhizal associations, climate, plant, and soil properties on the Nim:PNU ratio across terrestrial ecosystems. Our results show that mycorrhizal fungi type (arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi) in combination with soil inorganic N mainly explain the global variation in the Nim:PNU ratio in terrestrial ecosystems. In AM fungi‐associated ecosystems, the relationship between Nim and PNU displays a weaker negative correlation ( r = −.06, p r = .25, p

Addition of iron does not ameliorate sulfide toxicity by sargassum influx to mangroves but dampens methane and nitrous oxide emissions - Sara P. Cobacho; Luuk H. Leemans; Stefan T.J. Weideveld; Xitong Fu; Marieke M. van Katwijk; Leon P.M. Lamers; Alfons J.P. Smolders; Marjolijn J.A. Christianen (Marine Pollution Bulletin, 2024)

Reproducible responses of geochemical and microbial successional patterns in the subsurface to carbon source amendment - Jonathan P. Michael; Andrew D. Putt; Yunfeng Yang; Benjamin G. Adams; Kathryn R. McBride; Yupeng Fan; Kenneth A. Lowe; Daliang Ning; Sindhu Jagadamma; Ji Won Moon; Dawn M. Klingeman; Ping Zhang; et al. (Water Research, 2024)

A dynamic von Mises-based model to evaluate the impact of urbanization and climate change on flood timing in Yangtze and Huaihe River Basins, China - Pengcheng Xu; Dong Wang; Yuankun Wang; Vijay P. Singh; Zhilang Zhang; Xiaosan Shang; Hongyuan Fang; Yangyang Xie; Gengxi Zhang; Saiyan Liu; Xiaolei Fu (Journal of Hydrology, 2024)

Statistical reanalysis of Archean zircon paleointensities: No evidence for stagnant-lid tectonics - Roger R. Fu; Nadja Drabon; Benjamin P. Weiss; Cauê Borlina; Heather Kirkpatrick (Earth and Planetary Science Letters, 2024)

Uppermost global tree elevations are primarily limited by low temperature or insufficient moisture - Yuyang Xie; Zehao Shen; Tao Wang; George P. Malanson; Josep Peñuelas; Xiaoyi Wang; Xiangwu Chen; Eryuan Liang; Hongyan Liu; Mingzheng Yang; Lingxiao Ying; Fu Zhao; et al. (Global Change Biology, 2024)
The impact of anthropogenic global warming has induced significant upward dispersal of trees to higher elevations at alpine treelines. Assessing vertical deviation from current uppermost tree distributions to potential treeline positions is crucial for understanding ecosystem responses to evolving global climate. However, due to data resolution constraints and research scale limitation, comprehending the global pattern of alpine treeline elevations and driving factors remains challenging. This study constructed a comprehensive quasi‐observational dataset of uppermost tree distribution across global mountains using Google Earth imagery. Validating the isotherm of mean growing‐season air temperature at 6.6 ± 0.3°C as the global indicator of thermal treeline, we found that around two‐thirds of uppermost tree distribution records significantly deviated from it. Drought conditions constitute the primary driver in 51% of cases, followed by mountain elevation effect which indicates surface heat (27%). Our analyses underscore the multifaceted determinants of global patterns of alpine treeline, explaining divergent treeline responses to climate warming. Moisture, along with temperature and disturbance, plays the most fundamental roles in understanding global variation of alpine treeline elevation and forecasting alpine treeline response to ongoing global warming.

Synthesizing cationic polymers and tuning their properties for microalgae harvesting - Lisa Aditya; Hang P. Vu; Md Abu Hasan Johir; Shudi Mao; Ashley Ansari; Qiang Fu; Long D. Nghiem (Science of The Total Environment, 2024)

Bridging the gaps in cancer photothermal therapy through the intersection of nanotechnology and cell membrane coating - Shumin Yang; Huachun Pan; Blassan P. George; Xuanjian Fu; Hongwei Ma; Xiaojun Cai; Yang Chen; Qiang Cai; Quazi T.H. Shubhra (Chemical Engineering Journal, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

Functions and values of sulfated polysaccharides from seaweed - D. P. Nagahawatta; N. M. Liyanage; Thilina U. Jayawardena; Fengqi Yang; H. H. A. C. K. Jayawardena; M. J. M. S. Kurera; Fahe Wang; Xiaoting Fu; You-Jin Jeon (Algae, 2023)
Sulfated polysaccharides (SPs) isolated from seaweed have emerged as remarkable bioactive compounds with a wide spectrum of biological activities and have substantial value in the scientific and industrial domains. The current study explores the diverse biological activities of SPs and their relationship with their structures. This aids in an in-depth examination of the multifaceted biological activities of SPs, including anticoagulant, anti-inflammatory, antiviral, antioxidant, and immunomodulatory properties, which underpin their potential health benefits. Furthermore, the current study explores the complicated properties of SPs, with their extraction methodologies and techniques for precise characterization. Elucidation of the commercial significance of SPs derived from brown, red, and green seaweed by highlighting their potential applications has emphasized their importance in human well-being. Further, this review emphasizes the challenges needed to overcome research and industrial innovations for SPs. Collaboration among researchers, industry stakeholders, and regulatory authorities can overcome these challenges and elevate the potential of SPs to revolutionize industries such as pharmaceuticals, cosmeceuticals, food, and biotechnology.

A time-varying Copula-based approach to quantify the effects of antecedent drought on hot extremes - Pengcheng Xu; Zhilang Zhang; Dong Wang; Vijay P. Singh; Changsheng Zhang; Xiaolei Fu; Leizhi Wang (Journal of Hydrology, 2023)

A Review of the International Management Practice and Treatment Technology of Solid Waste Containing Perfluorooctane Sulfonic Acid - Jianying Fu; Shengdong Zhang; Mingxiu Zhan; Jinjian Ding; Xu Xu; Wenwen Ye; Hancheng Ma; Tong Chen; Wentao Jiao; Zheng Peng; John P. Giesy (Reviews of Environmental Contamination and Toxicology, 2023)

How does a celiac iceberg really float? The relationship between celiac disease and gluten - Xiaoxue Zhu; Xin-Huai Zhao; Qiang Zhang; Na Zhang; Olugbenga P. Soladoye; Rotimi E. Aluko; Yuhao Zhang; Yu Fu (Critical Reviews in Food Science and Nutrition, 2023)

Steady-state hydroelastic waves generated by a moving load in a uniform current - P. Wang; D.Q. Lu; L.D. Fu (Wave Motion, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Flavor mystery of spicy hot pot base: Chemical understanding of pungent, numbing, umami and fragrant characteristics - Bei Wang; Wei Wu; Jing Liu; Olugbenga P. Soladoye; Chi-Tang Ho; Yuhao Zhang; Yu Fu (Trends in Food Science & Technology, 2023)

Hepatotoxicity screening and ranking of structurally different pyrrolizidine alkaloids in zebrafish - Yueyang Pan; Jiang Ma; Hui Zhao; Peter P. Fu; Ge Lin (Food and Chemical Toxicology, 2023)

An optimization approach of water-food-energy nexus in agro-forestry-livestock system under uncertain water supply - Haiyan Li; Mo Li; Qiang Fu; Vijay P. Singh; Dong Liu; Yaowen Xu (Journal of Cleaner Production, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

Preparation of carbonaceous adsorption composite with refinery sludge for butyl xanthate and diethyldithiocarbamate removal in flotation wastewater - P. Fu; H. Yang; Q. Zhang; X. Li (International Journal of Environmental Science and Technology, 2023)

The potential meat flavoring generated from Maillard reaction products of wheat gluten protein hydrolysates-xylose: Impacts of different thermal treatment temperatures on flavor - Ao Sun; Lining Chen; Wei Wu; Olugbenga P. Soladoye; Yuhao Zhang; Yu Fu (Food Research International, 2023)

Factors influencing the transfer and abundance of antibiotic resistance genes in livestock environments in China - Z. F. Wang; H. Yun; S. Li; J. Ji; A. Khan; X. L. Fu; P. Zhang; X. K. Li (International Journal of Environmental Science and Technology, 2023)

Detection and attribution of urbanization impact on summer extreme heat based on nonstationary models in the Yangtze River Delta, China - Pengcheng Xu; Yuankun Wang; Xiaolei Fu; Vijay P. Singh; Jianchun Qiu (Urban Climate, 2023)

Informing the SWAT model with remote sensing detected vegetation phenology for improved modeling of ecohydrological processes - Shouzhi Chen; Yongshuo H. Fu; Zhaofei Wu; Fanghua Hao; Zengchao Hao; Yahui Guo; Xiaojun Geng; Xiaoyan Li; Xuan Zhang; Jing Tang; Vijay P. Singh; Xuesong Zhang (Journal of Hydrology, 2023)

Ecophysiological and genomic analyses of a representative isolate of highly abundant Bacillus cereus strains in contaminated subsurface sediments - Jennifer L. Goff; Elizabeth G. Szink; Michael P. Thorgersen; Andrew D. Putt; Yupeng Fan; Lauren M. Lui; Torben N. Nielsen; Kristopher A. Hunt; Jonathan P. Michael; Yajiao Wang; Daliang Ning; Ying Fu; et al. (Environmental Microbiology, 2022)
Bacillus cereus strain CPT56D‐587‐MTF (CPTF) was isolated from the highly contaminated Oak Ridge Reservation (ORR) subsurface. This site is contaminated with high levels of nitric acid and multiple heavy metals. Amplicon sequencing of the 16S rRNA genes (V4 region) in sediment from this area revealed an amplicon sequence variant (ASV) with 100% identity to the CPTF 16S rRNA sequence. Notably, this CPTF‐matching ASV had the highest relative abundance in this community survey, with a median relative abundance of 3.77% and comprised 20%–40% of reads in some samples. Pangenomic analysis revealed that strain CPTF has expanded genomic content compared to other B. cereus species—largely due to plasmid acquisition and expansion of transposable elements. This suggests that these features are important for rapid adaptation to native environmental stressors. We connected genotype to phenotype in the context of the unique geochemistry of the site. These analyses revealed that certain genes (e.g. nitrate reductase, heavy metal efflux pumps) that allow this strain to successfully occupy the geochemically heterogenous microniches of its native site are characteristic of the B. cereus species while others such as acid tolerance are mobile genetic element associated and are generally unique to strain CPTF.

Controlling Hydraulic Fracture Growth Through Precise Vertical Placement of Lateral Wells: Insights from HFTS Experiment and Numerical Validation - W. Fu; J. P. Morris; C. S. Sherman; P. Fu; J. Huang (Rock Mechanics and Rock Engineering, 2022)

Uncertainty of Gridded Precipitation at Local and Continent Scales: A Direct Comparison of Rainfall from SILO and AWAP in Australia - Guobin Fu; Olga Barron; Stephen P. Charles; Michael J. Donn; Thomas G. Van Niel; Geoff Hodgson (Asia-Pacific Journal of Atmospheric Sciences, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Role of Lysocardiolipin Acyltransferase in Cigarette Smoke-Induced Lung Epithelial Cell Mitochondrial ROS, Mitochondrial Dynamics, and Apoptosis - Mounica Bandela; Vidyani Suryadevara; Panfeng Fu; Sekhar P. Reddy; Kamesh Bikkavilli; Long Shuang Huang; Sugasini Dhavamani; Papasani V. Subbaiah; Sunit Singla; Steven M. Dudek; Lorraine B. Ware; Ramaswamy Ramchandran; et al. (Cell Biochemistry and Biophysics, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

The Santa Lúcia Cu-Au deposit, Carajás Mineral Province, Brazil: a Neoarchean (2.68 Ga) member of the granite-related copper-gold systems of Carajás - Raphael B. Hunger; Gustavo H. C. de Melo; Roberto P. Xavier; Carolina P. N. Moreto; Cristina Talavera; Zhi-Kun Su; Xin-Fu Zhao (Mineralium Deposita, 2021)

Developing urinary pyrrole–amino acid adducts as non-invasive biomarkers for identifying pyrrolizidine alkaloids-induced liver injury in human - Lin Zhu; Chunyuan Zhang; Wei Zhang; Qingsu Xia; Jiang Ma; Xin He; Yisheng He; Peter P. Fu; Wei Jia; Yuzheng Zhuge; Ge Lin (Archives of Toxicology, 2021)

Lean Stability Case Studies—Leveraging Science- and Risk-Based Approaches to Enable Meaningful Phase Specific Pharmaceutical Stability Strategies - Eric Adamec; Yelizaveta Babayan; Bruno Catacchio; Angela Coon; Allison Dill; Mingkun Fu; Lars Gruenig; Cherokee Hoaglund Hyzer; Michael Lesslie; Megan McMahon; Donnie Pulliam; Fenghe Qiu; et al. (Journal of Pharmaceutical Innovation, 2021)
Purpose Lean stability is a science- and risk-based initiative which utilizes the enhanced understanding of drug substance and drug product physical and chemical characteristics to (1) reduce and optimize the design of standard stability protocols; (2) expedite the generation of stability data without impact to safety, efficacy, or quality of the product; and (3) decrease time to market for innovative drugs. Lean stability was introduced in the early 2000s [ICH: Guideline Q1A(R2) (2003), ICH: Guideline Q1D (2002)] followed by reduced stability protocols, focusing on the critical quality attributes and critical time points, being reported in the literature [Skrdla et al. (J Pharm Biomed Anal 50: 794–796, 2009)]. While the concept of lean testing is not entirely new, and it is currently a part of several regulatory guidances, it continues to evolve and gain acceptance of the industry and regulators. Methods In this review, twelve case studies are presented where stability data was collected during clinical, registration, and post-approval phases of the product development. Results Case studies summarize the lean stability testing design, the strategies applied during the regulatory filing and the outcomes of the regulatory filings. Conclusion The authors expect that the case studies presented in this review will increase the visibility of lean stability, facilitate overcoming of the existing challenges, and accelerate the global regulatory acceptance of lean stability practices in the industry.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Nuclear Sphingosine-1-phosphate Lyase Generated ∆2-hexadecenal is A Regulator of HDAC Activity and Chromatin Remodeling in Lung Epithelial Cells - David L. Ebenezer; Ramaswamy Ramchandran; Panfeng Fu; Lizar A. Mangio; Vidyani Suryadevara; Alison W. Ha; Evgeny Berdyshev; Paul P. Van Veldhoven; Stephen J. Kron; Fabian Schumacher; Burkhard Kleuser; Viswanathan Natarajan (Cell Biochemistry and Biophysics, 2021)

An Enhanced Virtual Crack Closure Technique for Stress Intensity Factor Calculation along Arbitrary Crack Fronts and the Application in Hydraulic Fracturing Simulation - Hui Wu; Randolph R. Settgast; Pengcheng Fu; Joseph P. Morris (Rock Mechanics and Rock Engineering, 2021)

Gestational weight gain and risk of epithelial ovarian cancer - Zhuxuan Fu; Joseph L. Kelley; Kunle Odunsi; Robert P. Edwards; Kirsten Moysich; Francesmary Modugno (Cancer Causes & Control, 2021)

Optimization of agricultural water–food–energy nexus in a random environment: an integrated modelling approach - Mo Li; Vijay P. Singh; Qiang Fu; Dong Liu; Tianxiao Li; Yan Zhou (Stochastic Environmental Research and Risk Assessment, 2021)

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)

β-Adrenoceptor blockade prevents carotid body hyperactivity and elevated vascular sympathetic nerve density induced by chronic intermittent hypoxia - Abdulaziz A. Alzahrani; Lily L. Cao; Hayyaf S. Aldossary; Demitris Nathanael; Jiarong Fu; Clare J. Ray; Keith L. Brain; Prem Kumar; Andrew M. Coney; Andrew P. Holmes (Pflügers Archiv - European Journal of Physiology, 2021)
Carotid body (CB) hyperactivity promotes hypertension in response to chronic intermittent hypoxia (CIH). The plasma concentration of adrenaline is reported to be elevated in CIH and our previous work suggests that adrenaline directly activates the CB. However, a role for chronic adrenergic stimulation in mediating CB hyperactivity is currently unknown. This study evaluated whether beta-blocker treatment with propranolol (Prop) prevented the development of CB hyperactivity, vascular sympathetic nerve growth and hypertension caused by CIH. Adult male Wistar rats were assigned into 1 of 4 groups: Control (N), N + Prop, CIH and CIH + Prop. The CIH paradigm consisted of 8 cycles h −1 , 8 h day −1 , for 3 weeks. Propranolol was administered via drinking water to achieve a dose of 40 mg kg −1 day −1 . Immunohistochemistry revealed the presence of both β 1 and β 2 -adrenoceptor subtypes on the CB type I cell. CIH caused a 2–3-fold elevation in basal CB single-fibre chemoafferent activity and this was prevented by chronic propranolol treatment. Chemoafferent responses to hypoxia and mitochondrial inhibitors were attenuated by propranolol, an effect that was greater in CIH animals. Propranolol decreased respiratory frequency in normoxia and hypoxia in N and CIH. Propranolol also abolished the CIH mediated increase in vascular sympathetic nerve density. Arterial blood pressure was reduced in propranolol groups during hypoxia. Propranolol exaggerated the fall in blood pressure in most (6/7) CIH animals during hypoxia, suggestive of reduced sympathetic tone. These findings therefore identify new roles for β-adrenergic stimulation in evoking CB hyperactivity, sympathetic vascular hyperinnervation and altered blood pressure control in response to CIH.

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Maillard reaction products derived from food protein-derived peptides: insights into flavor and bioactivity - Yu Fu; Yuhao Zhang; Olugbenga P. Soladoye; Rotimi E. Aluko (Critical Reviews in Food Science and Nutrition, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Differential effects of various genetic mouse models of the mechanistic target of rapamycin complex I inhibition on heart failure - Dao-Fu Dai; Yonggang Liu; Nathan Basisty; Pabalu Karunadharma; Somasish G. Dastidar; Ying Ann Chiao; Tony Chen; Richard P. Beyer; Michael T. Chin; Michael Maccoss; Albert R. La Spada; Peter S. Rabinovitch (GeroScience, 2019)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Evaluating a Simple Fracturing Criterion for a Hydraulic Fracture Crossing Stress and Stiffness Contrasts - Jixiang Huang; Pengcheng Fu; Randolph R. Settgast; Joseph P. Morris; Frederick J. Ryerson (Rock Mechanics and Rock Engineering, 2019)

Identification of Gangesia oligonchis Roitman & Freze, 1964 (Cestoda: Onchoproteocephalidea) from Tachysurus fulvidraco Richardson in central China: implications for the validity of Gangesia pseudobagrae Chen, 1962 - Pei P. Fu; Wen X. Li; Hong Zou; Dong Zhang; Shan G. Wu; Ming Li; Gui T. Wang; Bing W. Xi (Systematic Parasitology, 2019)

Improving the knowledge and behavior of workplace chemical exposures in Vietnamese–American nail salon workers: a randomized controlled trial - Thu Quach; J. Von Behren; J. Tsoh; P. Reynolds; L. Fu; T. Nguyen; M. Le; T. T. Nguyen (International Archives of Occupational and Environmental Health, 2018)

The role of formation of pyrrole–ATP synthase subunit beta adduct in pyrrolizidine alkaloid-induced hepatotoxicity - Yao Lu; Jiang Ma; Zijing Song; Yang Ye; Peter P. Fu; Ge Lin (Archives of Toxicology, 2018)

Quantitative discrimination of normal fault segment growth and its geological significance: example from the Tanan Depression, Tamtsag Basin, Mongolia - H. X. Wang; X. F. Fu; S. R. Liu; R. Chu; B. Liu; P. P. Shi (Australian Journal of Earth Sciences, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Field-Based Radiographic Imaging of Marine Megafauna: Marine Iguanas (Amblyrhynchus cristatus) as a Case Study - Gregory A. Lewbart; Eli B. Cohen; Maximilian Hirschfeld; Juan Pablo Muñoz-Pérez; Juan García; Andy Fu; Emile P. Chen; Kenneth J. Lohmann (Frontiers in Marine Science, 2018)

Influences of environmental factors on biomass of phytoplankton in the northern part of Tai Lake, China, from 2000 to 2012 - Wenjing Guo; Yuanrong Zhu; Zhiyou Fu; Ning Qin; Hao Wang; Shasha Liu; Yan Hu; Fengchang Wu; John P. Giesy (Environmental Monitoring and Assessment, 2017)

Serum global metabolomics profiling reveals profound metabolic impairments in patients with MPS IIIA and MPS IIIB - Haiyan Fu; Aaron S. Meadows; Ricardo J. Pineda; Robert P. Mohney; Steve Stirdivant; Douglas M. McCarty (Metabolic Brain Disease, 2017)

An anoxic-aerobic system for simultaneous biodegradation of phenol and ammonia in a sequencing batch reactor - Qifeng Liu; Vijay P. Singh; Zhimin Fu; Jing Wang; La Hu (Environmental Science and Pollution Research, 2017)

The long persistence of pyrrolizidine alkaloid-derived DNA adducts in vivo: kinetic study following single and multiple exposures in male ICR mice - Lin Zhu; Junyi Xue; Qingsu Xia; Peter P. Fu; Ge Lin (Archives of Toxicology, 2017)

Differences between serum polar lipid profiles of male and female rheumatoid arthritis patients in response to glucocorticoid treatment - Junzeng Fu; Bart V. J. Cuppen; Paco M. J. Welsing; Herman van Wietmarschen; Amy C. Harms; Ruud Berger; Slavik Koval; Ruth D. E. Fritsch-Stork; Johannes W. J. Bijlsma; Thomas Hankemeier; Jan van der Greef; Floris P. J. G. Lafeber (Inflammopharmacology, 2016)

High-density marker profiling confirms ancestral genomes of Avena species and identifies D-genome chromosomes of hexaploid oat - Honghai Yan; Wubishet A. Bekele; Charlene P. Wight; Yuanying Peng; Tim Langdon; Robert G. Latta; Yong-Bi Fu; Axel Diederichsen; Catherine J. Howarth; Eric N. Jellen; Brian Boyle; Yuming Wei; et al. (Theoretical and Applied Genetics, 2016)

Impact of Partially Cemented and Non-persistent Natural Fractures on Hydraulic Fracture Propagation - Wei Fu; Brandon C. Ames; Andrew P. Bunger; Alexei A. Savitski (Rock Mechanics and Rock Engineering, 2016)

Osteogenic Treatment Initiating a Tissue-Engineered Cartilage Template Hypertrophic Transition - J. Y. Fu; S. Y. Lim; P. F. He; C. J. Fan; D. A. Wang (Annals of Biomedical Engineering, 2016)

Fast neutron-induced structural rearrangements at a soybean NAP1 locus result in gnarled trichomes - Benjamin W. Campbell; Anna N. Hofstad; Suma Sreekanta; Fengli Fu; Thomas J. Y. Kono; Jamie A. O’Rourke; Carroll P. Vance; Gary J. Muehlbauer; Robert M. Stupar (Theoretical and Applied Genetics, 2016)

Cocaine-Mediated Autophagy in Astrocytes Involves Sigma 1 Receptor, PI3K, mTOR, Atg5/7, Beclin-1 and Induces Type II Programed Cell Death - Lu Cao; Mary P. Walker; Naveen K. Vaidya; Mingui Fu; Santosh Kumar; Anil Kumar (Molecular Neurobiology, 2016)

Effect of Selenium Against Lead-Induced Damage on the Gene Expression of Heat Shock Proteins and Inflammatory Cytokines in Peripheral Blood Lymphocytes of Chickens - G.X. Sun; Y. Chen; C. P. Liu; S. Li; J. Fu (Biological Trace Element Research, 2016)

Effects of Dietary Selenium Against Lead Toxicity on mRNA Levels of 25 Selenoprotein Genes in the Cartilage Tissue of Broiler Chicken - H Gao; C. P. Liu; S. Q. Song; J. Fu (Biological Trace Element Research, 2016)

Histamine induces the production of matrix metalloproteinase-9 in human astrocytic cultures via H1-receptor subtype - Aarti Patel; Vishnu Vasanthan; Wen Fu; Richard P. Fahlman; David MacTavish; Jack H. Jhamandas (Brain Structure and Function, 2016)

Identification and Functional Prediction of Large Intergenic Noncoding RNAs (lincRNAs) in Rainbow Trout (Oncorhynchus mykiss) - Jian Wang; Liyuan Fu; Prasanthi P. Koganti; Lei Wang; Jacqelyn M. Hand; Hao Ma; Jianbo Yao (Marine Biotechnology, 2016)

Comparison of NCEP ‐ NCAR and ERA ‐Interim over Australia - Guobin Fu; Stephen P. Charles; Bertrand Timbal; Branislava Jovanovic; Fen Ouyang (International Journal of Climatology, 2016)
This study compares observations of 22 climate variables [rainfall, minimum and maximum temperature, mean sea level pressure (MSLP), and air temperature, geopotential heights, relative and specific humidity, and u‐wind and v‐winds at 500 , 700 and 850 hPa] over Australia with NCEP‐NCAR (National Centers for Environmental Prediction‐National Center for Atmospheric Research) and ERA ‐Interim, two most often used reanalysis products. The results indicate that both NCEP‐NCAR and ERA ‐Interim generally reproduce the observed spatial patterns of long‐term mean annual rainfall, daily maximum/minimum temperature and MSLP, the monthly distribution (annual cycle) of rainfall and temperature, although temperature is generally better simulated than rainfall and ERA ‐Interim shows an overall better performance than NCEP‐NCAR in term of continental scale. In term of linear trends, both NCEP‐NCAR and ERA ‐Interim simulate observed trend signs in some regions, but not in others, and the spatial distributions of temperature trends are generally not as well simulated as that of annual rainfall for both NCEP‐NCAR and ERA ‐Interim. In addition, NCEP‐NCAR and ERA ‐Interim show similar spatial patterns of annual mean air temperature, geopotential heights, humidity and winds. This implies that studies using NCEP‐NCAR data could also make use of ERA ‐Interim to explore the range of uncertainties for the regions and climate variables where NCEP‐NCAR and ERA ‐Interim show differences. This conclusion may also apply to regions other than Australia. For example, the different trend signs of MSLP between NCEP‐NCAR and ERA ‐Interim could present a scientific challenging for climatic change studies using MSLP trends, and the split between large‐scale and convective rainfall would also have merits globally to understand if the differences between the two reanalysis data sets are global or if we see convergence on key areas, such as tropices and frontal systems.

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Transport of short-chain perfluoroalkyl acids from concentrated fluoropolymer facilities to the Daling River estuary, China - Pei Wang; Yonglong Lu; Tieyu Wang; Zhaoyun Zhu; Qifeng Li; Yueqing Zhang; Yaning Fu; Yang Xiao; John P. Giesy (Environmental Science and Pollution Research, 2015)

Association of genetic variation in IKZF1, ARID5B, and CEBPE and surrogates for early-life infections with the risk of acute lymphoblastic leukemia in Hispanic children - Ling-I. Hsu; Anand P. Chokkalingam; Farren B. S. Briggs; Kyle Walsh; Vonda Crouse; Cecilia Fu; Catherine Metayer; Joseph L. Wiemels; Lisa F. Barcellos; Patricia A. Buffler (Cancer Causes & Control, 2015)

The role of heat shock proteins in oxidative stress damage induced by Se deficiency in chicken livers - C. P. Liu; J. Fu; F. P. Xu; X. S. Wang; S. Li (BioMetals, 2015)

Zircon U–Pb, O, and Hf isotopic constraints on Mesozoic magmatism in the Cyclades, Aegean Sea, Greece - Bin Fu; Michael Bröcker; Trevor Ireland; Peter Holden; Leslie P. J. Kinsley (International Journal of Earth Sciences, 2015)

Accuracy and Reproducibility of Patient-Specific Hemodynamic Models of Stented Intracranial Aneurysms: Report on the Virtual Intracranial Stenting Challenge 2011 - S. Cito; A. J. Geers; M. P. Arroyo; V. R. Palero; J. Pallarés; A. Vernet; J. Blasco; L. San Román; W. Fu; A. Qiao; G. Janiga; Y. Miura; et al. (Annals of Biomedical Engineering, 2015)

Thai elite cassava genetic diversity was fortuitously conserved through farming with different sets of varieties - Yong-Bi Fu; Preeya P. Wangsomnuk; Benjawan Ruttawat (Conservation Genetics, 2014)

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

The role of HIF1α in renal cell carcinoma tumorigenesis - Lorraine J. Gudas; Leiping Fu; Denise R. Minton; Nigel P. Mongan; David M. Nanus (Journal of Molecular Medicine, 2014)

Effects of Dietary Selenium Deficiency on mRNA Levels of Twenty-One Selenoprotein Genes in the Liver of Layer Chicken - C. P. Liu; J. Fu; S. L. Lin; X. S. Wang; S. Li (Biological Trace Element Research, 2014)

An analysis of the drought and flood hazard characteristics and risks during the pre-rainy season in South China - L. P. Li; K. M. Zhang; T. Luo; Xiouhua Fu (Natural Hazards, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Understanding Human–Landscape Interactions in the “Anthropocene” - Carol P. Harden; Anne Chin; Mary R. English; Rong Fu; Kathleen A. Galvin; Andrea K. Gerlak; Patricia F. McDowell; Dylan E. McNamara; Jeffrey M. Peterson; N. LeRoy Poff; Eugene A. Rosa; William D. Solecki; et al. (Environmental Management, 2014)

Wood chemistry analysis and expression profiling of a poplar clone expressing a tyrosine-rich peptide - Yi Xu; Chin-Fu Chen; Tina P. Thomas; Parastoo Azadi; Brett Diehl; Chung-Jui Tsai; Nicole Brown; John E. Carlson; Ming Tien; Haiying Liang (Plant Cell Reports, 2013)

A Factorial-based Dynamic Analysis Method for Reservoir Operation Under Fuzzy-stochastic Uncertainties - D. Z. Fu; Y. P. Li; G. H. Huang (Water Resources Management, 2013)

Scanning Electron Microscopy Studies of the Antennal Sensilla of Metaphycus parasaissetiae Zhang & Huang (Hymenoptera: Encyrtidae) - H Zhou; W J Wu; F P Zhang; Y G Fu (Neotropical Entomology, 2013)

The Effect of Stress-Induced Senescence on Aging Human Cord Blood-Derived Endothelial Cells - Tracy M. Cheung; Mansi P. Ganatra; Justin J. Fu; George A. Truskey (Cardiovascular Engineering and Technology, 2013)

Scl gene construction, expression and effect on hemangioma - H. X. Yin; Z. H. Zhang; J. C. Shen; A. L. Zhang; T. Y. Zhang; J. X. Luo; C. Y. Fu; X. P. Yi; Z. W. Liu; S. S. Yang; B. Zhou; X. Fu (Molecular Biology Reports, 2013)

A comparison of three multi-site statistical downscaling models for daily rainfall in the North China Plain - Wenbin Liu; Guobin Fu; Changming Liu; Stephen P. Charles (Theoretical and Applied Climatology, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Characterization and expression of Cd8 molecules in mandarin fish Siniperca chuatsi - Z. Guo; G. L. Wang; J. P. Fu; P. Nie (Journal of Fish Biology, 2013)
The full‐length complementary DNA (cDNA) sequences encoding cd8α and cd8β molecules were sequenced and characterized from mandarin fish Siniperca chuatsi . Conserved motifs and residues were found to be present in derived peptides of the Cd8 molecules. For example, WXR motif, DXGXYXC motif, and four cysteine residues were present in the extracellular region of the Cd8 protein. Threonine, serine and proline residues involved in multiple O ‐linked glycosylation events were located in the membrane proximal hinge region. The common CPH motif in the cytoplasmic tail was detected similar to other teleost Cd8 molecules. Different from those in mammals, S. chuatsi Cd8 sequences have many extra cysteine residues (C149 in Cd8 α sequence and C46, C51 and C158 in Cd8 β sequence), which also exist in other teleost Cd8 molecules. Real‐time polymerase chain reaction (RT‐PCR) and Western blot analyses revealed that the thymus had the highest expression of cd8 messenger (m)RNA and protein. After stimulated with phytohaemagglutinin, polyriboinsine‐polyribocyaidylic acid and concanavalin A (ConA), the expression level of cd8 mRNA increased significantly in head‐kidney lymphocytes at 4 and 8 h, but decreased to normal level at 12 h. Similarly, stimulation with ConA in vivo also led to an increase in the cd8 mRNA level in the spleen. Immunohistochemistry analysis demonstrated that Cd8 α ‐positive cells can be detected in the thymus, spleen and intestine by using polyclonal anti‐Cd8 α antibody.

Grain and shoot zinc accumulation in winter wheat affected by nitrogen management - Yan-Fang Xue; Shan-Chao Yue; Yue-Qiang Zhang; Zhen-Ling Cui; Xin-Ping Chen; Fu-Chun Yang; Ismail Cakmak; Steve P. McGrath; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2012)

Constitutive expression of barley α-amylase in Pichia pastoris by high-density cell culture - Z. W. Liu; H. X. Yin; X. P. Yi; A. L. Zhang; J. X. Luo; T. Y. Zhang; C. Y. Fu; Z. H. Zhang; J. C. Shen; L. P. Chen (Molecular Biology Reports, 2012)

A fuzzy-Markov-chain-based analysis method for reservoir operation - D. Z. Fu; Y. P. Li; G. H. Huang (Stochastic Environmental Research and Risk Assessment, 2012)

New constraints on fluid sources in orogenic gold deposits, Victoria, Australia - Bin Fu; Mark A. Kendrick; Alison M. Fairmaid; David Phillips; Christopher J. L. Wilson; Terrence P. Mernagh (Contributions to Mineralogy and Petrology, 2012)

Competitive interactions in Ginkgo and crop species mixed agroforestry systems in Jiangsu, China - Fu-liang Cao; J. P. Kimmins; J. R. Wang (Agroforestry Systems, 2012)

Evaluation of two statistical downscaling models for daily precipitation over an arid basin in China - Zhaofei Liu; Zongxue Xu; Stephen P. Charles; Guobin Fu; Liu Liu (International Journal of Climatology, 2011)
Two statistical downscaling (SD) models, the nonhomogeneous hidden Markov model (NHMM) and the statistical down‐scaling model (SDSM), which have been widely applied and proved skillful in terms of downscaling precipitation, were evaluated based on observed daily precipitation over the Tarim River basin, an arid basin located in China. The evaluated metrics included residual functions, correlation analyses, probability density functions (PDFs) and distributions. Overall, both models exhibited stability with little model performance difference between the calibration and validation periods. There was little difference for model performance on dry‐spell length (dsl) and wet‐spell length (wsl) between NHMM and SDSM. NHMM showed skill in simulating wet‐day precipitation amount (wpa), whilst SDSM performed relatively poorly on extreme values of wpa, especially for dry stations with annual precipitation lower than 200 mm. Both NHMM and SDSM captured the spatial distribution characteristics of precipitation for most of the stations, as 11 months had an at‐station correlation coefficient being greater than 0.9 and 0.8 for NHMM and SDSM in calibration period. NHMM showed slightly better model performance than SDSM on simulating monthly precipitation, as the former was able to model precipitation well for all months, whereas the later was well only for certain months. SDSM was able to capture the inter‐site correlation characteristics of observed series, whilst the NHMM multi‐site simulation over estimated inter‐site correlation. Both NHMM and SDSM had less skill downscaling annual series because of stochastic components in precipitation amounts modelling. Copyright © 2011 Royal Meteorological Society

Portal protein diversity and phage ecology - Matthew B. Sullivan; Maureen L. Coleman; Vanessa Quinlivan; Jessica E. Rosenkrantz; Alicia S. DeFrancesco; G. Tan; Ross Fu; Jessica A. Lee; John B. Waterbury; Joseph P. Bielawski; Sallie W. Chisholm (Environmental Microbiology, 2011)

Spatial heterogeneity of bacterial community structure in the sediments of the Pearl River estuary - Fu-Lin Sun; You-Shao Wang; Mei-Lin Wu; Yu-Tu Wang; Qian P. Li (Biologia, 2011)

Activation of group IVC phospholipase A2 by polycyclic aromatic hydrocarbons induces apoptosis of human coronary artery endothelial cells - Patricia K. Tithof; Sean M. Richards; Mona A. Elgayyar; Fu-Minn Menn; Vijay M. Vulava; Larry McKay; John Sanseverino; Gary Sayler; Dawn E. Tucker; Christina C. Leslie; Kim P. Lu; Kenneth S. Ramos (Archives of Toxicology, 2011)

Land Use-Based Landscape Planning and Restoration in Mine Closure Areas - Jianjun Zhang; Meichen Fu; Ferri P. Hassani; Hui Zeng; Yuhuan Geng; Zhongke Bai (Environmental Management, 2011)

Towards a custom chelator for mercury: evaluation of coordination environments by molecular modeling - Juxia Fu; Ruth E. Hoffmeyer; M. Jake Pushie; Satya P. Singh; Ingrid J. Pickering; Graham N. George (JBIC Journal of Biological Inorganic Chemistry, 2011)

Comparative Life Cycle Assessment of Lignocellulosic Ethanol Production: Biochemical Versus Thermochemical Conversion - Dongyan Mu; Thomas Seager; P. Suresh Rao; Fu Zhao (Environmental Management, 2010)

OSTM/Jason-2: Assessment of the System Performances (Ocean Surface Topography Mission: OSTM) - G. Zaouche; J. Perbos; T. Lafon; V. Couderc; J. Lambin; J. D. Desjonqueres; C. Jayles; E. Jurado; P. Vaze; L.-L. Fu; S. Brown; F. Parisot; et al. (Marine Geodesy, 2010)

Relative competitive abilities and productivity in Ginkgo and broad bean and wheat mixtures in southern China - Fu-liang Cao; J. P. Kimmins; P. A. Jolliffe; J. R. Wang (Agroforestry Systems, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Evaluation of various root transformations of daily precipitation amounts fitted with a normal distribution for Australia - Guobin Fu; Neil R. Viney; Stephen P. Charles (Theoretical and Applied Climatology, 2010)

A critical overview of pan evaporation trends over the last 50 years - Guobin Fu; Stephen P. Charles; Jingjie Yu (Climatic Change, 2009)

Co-localization of hyperphosphorylated tau and caspases in the brainstem of Alzheimer’s disease patients - Maria Sen Mun Wai; Yong Liang; Chun Shi; Eric Y. P. Cho; Hsiang-fu Kung; David T. Yew (Biogerontology, 2009)

Advance and prospectus of seasonal prediction: assessment of the APCC/CliPAS 14-model ensemble retrospective seasonal prediction (1980–2004) - Bin Wang; June-Yi Lee; In-Sik Kang; J. Shukla; C.-K. Park; A. Kumar; J. Schemm; S. Cocke; J.-S. Kug; J.-J. Luo; T. Zhou; B. Wang; et al. (Climate Dynamics, 2009)

Avian comparative genomics: reciprocal chromosome painting between domestic chicken (Gallus gallus) and the stone curlew (Burhinus oedicnemus, Charadriiformes)—An atypical species with low diploid number - Wenhui Nie; Patricia C. M. O’Brien; Bee L. Ng; Beiyuan Fu; Vitaly Volobouev; Nigel P. Carter; Malcolm A. Ferguson-Smith; Fengtang Yang (Chromosome Research, 2009)

Portal protein diversity and phage ecology - Matthew B. Sullivan; Maureen L. Coleman; Vanessa Quinlivan; Jessica E. Rosenkrantz; Alicia S. DeFrancesco; G. Tan; Ross Fu; Jessica A. Lee; John B. Waterbury; Joseph P. Bielawski; Sallie W. Chisholm (Environmental Microbiology, 2008)
Summary Oceanic phages are critical components of the global ecosystem, where they play a role in microbial mortality and evolution. Our understanding of phage diversity is greatly limited by the lack of useful genetic diversity measures. Previous studies, focusing on myophages that infect the marine cyanobacterium Synechococcus , have used the coliphage T4 portal‐protein‐encoding homologue, gene 20 ( g20 ), as a diversity marker. These studies revealed 10 sequence clusters, 9 oceanic and 1 freshwater, where only 3 contained cultured representatives. We sequenced g20 from 38 marine myophages isolated using a diversity of Synechococcus and Prochlorococcus hosts to see if any would fall into the clusters that lacked cultured representatives. On the contrary, all fell into the three clusters that already contained sequences from cultured phages. Further, there was no obvious relationship between host of isolation, or host range, and g20 sequence similarity. We next expanded our analyses to all available g20 sequences (769 sequences), which include PCR amplicons from wild uncultured phages, non‐PCR amplified sequences identified in the Global Ocean Survey (GOS) metagenomic database, as well as sequences from cultured phages, to evaluate the relationship between g20 sequence clusters and habitat features from which the phage sequences were isolated. Even in this meta‐data set, very few sequences fell into the sequence clusters without cultured representatives, suggesting that the latter are very rare, or sequencing artefacts. In contrast, sequences most similar to the culture‐containing clusters, the freshwater cluster and two novel clusters, were more highly represented, with one particular culture‐containing cluster representing the dominant g20 genotype in the unamplified GOS sequence data. Finally, while some g20 sequences were non‐randomly distributed with respect to habitat, there were always numerous exceptions to general patterns, indicating that phage portal proteins are not good predictors of a phage's host or the habitat in which a particular phage may thrive.

Importance of Small Pores in Microcrystalline Cellulose for Controlling Water Distribution during Extrusion–Spheronization - Josephine L. P. Soh; Lei Yang; Celine V. Liew; Fu D. Cui; Paul W. S. Heng (AAPS PharmSciTech, 2008)

Trade-offs between constitutive and induced resistance in wild crucifers shown by a natural, but not an artificial, elicitor - Peng-Jun Zhang; Jin-Ping Shu; Cheng-Xin Fu; Yun Zhou; Ying Hu; Myron P. Zalucki; Shu-Sheng Liu (Oecologia, 2008)

Simulation of direct effects of black carbon aerosol on temperature and hydrological cycle in Asia by a Regional Climate Model - J. Wu; C. Fu; Y. Xu; J. P. Tang; W. Wang; Z. Wang (Meteorology and Atmospheric Physics, 2008)

Public-Private Partnerships in China’s Urban Water Sector - Lijin Zhong; Arthur P. J. Mol; Tao Fu (Environmental Management, 2008)

Genealogical relationships of southern Ontario polyploid unisexual salamanders (genus Ambystoma) inferred from intergenomic exchanges and major rDNA cytotypes - Ke Bi; James P. Bogart; Jinzhong Fu (Chromosome Research, 2008)

Genealogical relationships of southern Ontario polyploid unisexual salamanders (genus Ambystoma) inferred from intergenomic exchanges and major rDNA cytotypes - Ke Bi; James P. Bogart; Jinzhong Fu (Chromosome Research, 2008)

Response of Brassica napus and B. juncea germplasm from Australia, China and India to Australian populations of Leptosphaeria maculans - C. X. Li; N. Wratten; P. A. Salisbury; W. A. Burton; T. D. Potter; G. Walton; Hua Li; K. Sivasithamparam; Surinder S. Banga; Shashi Banga; D. Singh; S. Y. Liu; et al. (Australasian Plant Pathology, 2008)

Physcomitrella patens arabinogalactan proteins contain abundant terminal 3-O-methyl-l-rhamnosyl residues not found in angiosperms - Hu Fu; Madhav P. Yadav; Eugene A. Nothnagel (Planta, 2007)

Two new flavanes and bioactive compounds from Daphne tangutica Maxim - W. Zhang; Y. H. Shen; Z. Y. Lou; R. H. Liu; C. Zhang; P. Fu; L. Shan; W. D. Zhang (Natural Product Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Molecular characterization of the surface glycoprotein genes of an H5N1 influenza virus isolated from a human in Guangdong, China - J.-J. Zhou; J. Fu; D.-Y. Fang; H.-J. Yan; J. Tian; J.-M. Zhou; J.-P. Tao; Y. Liang; L.-F. Jiang (Archives of Virology, 2007)

CO 2 control of Trichodesmium N 2 fixation, photosynthesis, growth rates, and elemental ratios: Implications for past, present, and future ocean biogeochemistry - D. A. Hutchins; F.-X. Fu; Y. Zhang; M. E. Warner; Y. Feng; K. Portune; P. W. Bernhardt; M. R. Mulholland (Limnology and Oceanography, 2007)
Diazotrophic marine cyanobacteria in the genus Trichodesmium contribute a large fraction of the new nitrogen entering the oligotrophic oceans, but little is known about how they respond to shifts in global change variables such as carbon dioxide (CO 2 ) and temperature. We compared Trichodesmium dinitrogen (N 2 ) and CO 2 fixation rates during steady‐state growth under past, current, and future CO 2 scenarios, and at two relevant temperatures. At projected CO 2 levels of year 2100 (76 Pa, 750 ppm), N 2 fixation rates of Pacific and Atlantic isolates increased 35–100%, and CO 2 fixation rates increased 15‐128% relative to present day CO 2 conditions (39 Pa, 380 ppm). CO 2 ‐mediated rate increases were of similar relative magnitude in both phosphorus (P)‐replete and P‐limited cultures, suggesting that this effect may be independent of resource limitation. Neither isolate could grow at 15 Pa (150 ppm) CO 2 , but N 2 and CO 2 fixation rates, growth rates, and nitrogen : phosophorus (N : P) ratios all increased significantly between 39 Pa and 152 Pa (1500 ppm). In contrast, these parameters were affected only minimally or not at all by a 4°C temperature change. Photosynthesis versus irradiance parameters, however, responded to both CO 2 and temperature but in different ways for each isolate. These results suggest that by the end of this century, elevated CO 2 could substantially increase global Trichodesmium N 2 and CO 2 fixation, fundamentally altering the current marine N and C cycles and potentially driving some oceanic regimes towards P limitation. CO 2 limitation of Trichodesmium diazotrophy during past glacial periods could also have contributed to setting minimum atmospheric CO 2 levels through downregulation of the biological pump. The relationship between marine N 2 fixation and atmospheric CO 2 concentration appears to be more complex than previously realized and needs to be considered in the context of the rapidly changing oligotrophic oceans.

Composition and antimicrobial activity of the essential oil of Actinidia macrosperma from China - Y. Lu†; Y. P. Zhao†; Z. C. Wang; S. Y. Chen; C. X. Fu* (Natural Product Research, 2007)

Two new chemical constituents from Daphne odora Thunb. var. marginata - W. Zhang; W. D. Zhang; R. H. Liu; Y. H. Shen; C. Zhang; H. S. Cheng; P. Fu; L. Shan (Natural Product Research, 2006)

Two new xanthones from Hypericum japonicum - P. Fu; W.-D. Zhang; R. H. Liu; T.-Z. Li; Y.-H. Shen; H.-L. Li; W. Zhang; H.-S. Chen (Natural Product Research, 2006)

Geochemical evidence for the variation of historical seabird population on Dongdao Island of the South China Sea - X. D. Liu; S. P. Zhao; L. G. Sun; H. H. Luo; X. B. Yin; Z. Q. Xie; Y. H. Wang; K. X. Liu; X. H. Wu; X. F. Ding; D. P. Fu (Journal of Paleolimnology, 2006)

An unexpected recent ancestor of unisexual Ambystoma - ALEXANDER V. ROBERTSON; CADHLA RAMSDEN; JOHN NIEDZWIECKI; JINZHONG FU; JAMES P. BOGART (Molecular Ecology, 2006)
Previous research has shown that members of the unisexual hybrid complex of the genus Ambystoma possess a mitochondrial genome that is unrelated to their nuclear parental species, but the origin of this mitochondrion has remained unclear. We used a 744‐bp fragment of the mitochondrial gene cytochrome b within a comparative phylogenetic framework to infer the maternal ancestor of this unisexual lineage. By examining a broader range of species than has previously been compared, we were able to uncover a recent maternal ancestor to this complex. Unexpectedly, Ambystoma barbouri , a species whose nuclear DNA has not been identified in the unisexuals, was found to be the recent maternal ancestor of the individuals examined through the discovery of a shared mtDNA haplotype between the unisexuals and A. barbouri. Based on a combination of sequence data and glacial patterning, we estimate that the unisexual lineage probably originated less than 25 000 years ago. In addition, all unisexuals examined showed extremely similar mtDNA sequences and the resultant phylogeny was consistent with a single origin for this lineage. These results confirm previous suggestions that the unisexual Ambystoma complex was formed from a hybridization event in which the nuclear DNA of the original maternal species was subsequently lost.

Effect of acute tryptophan depletion on pre-frontal engagement - Paul P. Allen; Anthony J. Cleare; Francis Lee; Paolo Fusar-Poli; Nigel Tunstall; Cynthia H. Y. Fu; Micheal J. Brammer; Philip K. McGuire (Psychopharmacology, 2006)

Successful implantation of intravenously administered stem cells correlates with severity of inflammation in murine myocarditis - Sohail Malek; Emel Kaplan; Ju-Feng Wang; Qingen Ke; Jamal S. Rana; Yu Chen; Bilal G. Rahim; Ma Li; Qin Huang; Yong-Fu Xiao; Freek W. A. Verheugt; James P. Morgan; et al. (Pflügers Archiv - European Journal of Physiology, 2006)

The systematic value of pollen morphology in Smilacaceae - S.-C. Chen; X.-P. Zhang; S.-F. Ni; C.-X. Fu; K. M. Cameron (Plant Systematics and Evolution, 2006)

Effects of ketamine on prefrontal and striatal regions in an overt verbal fluency task: a functional magnetic resonance imaging study - Cynthia H. Y. Fu; Kathryn M. Abel; Matthew P. G. Allin; David Gasston; Sergi G. Costafreda; John Suckling; Steve C. R. Williams; Philip K. McGuire (Psychopharmacology, 2005)

Postglacial colonization of the Tibetan plateau inferred from the matrilineal genetic structure of the endemic red‐necked snow finch, Pyrgilauda ruficollis - YAN HUA QU; PER G. P. ERICSON; FU MIN LEI; SHOU HSIEN LI (Molecular Ecology, 2005)
Most phylogeographical studies of postglacial colonization focus on high latitude locations in the Northern Hemisphere. Here, we studied the phylogeographical structure of the red‐necked snow finch Pyrgilauda ruficollis , an endemic species of the Tibetan plateau. We analysed 879 base pairs (bp) of the mitochondrial cytochrome b gene and 529 bp of the control region in 41 birds from four regional groups separated by mountain ranges. We detected 34 haplotypes, 31 of which occurred in a single individual and only three of which were shared among sampling sites within regional groups or among regional groups. Haplotype diversity was high ( h = 0.94); nucleotide diversity was low (ð = 0.00415) and genetic differentiation was virtually non‐existent. Analyses of mismatch distributions and geographically nested clades yielded results consistent with contiguous range expansion, and the expansion times were estimated as 0.07–0.19 million years ago (Ma). Our results suggest that P. ruficollis colonized the Tibetan plateau after the extensive glacial period (0.5–0.175 Ma), expanding from the eastern margin towards the inner plateau. Thus, in contrast to many of the postglacial phylogeographical structures known at high latitudes, this colonization occurred without matrilineal population structuring. This might be due to the short glacial cycles typical of the Tibetan plateau, adaptation of P. ruficollis to cold conditions, or refugia and colonized habitat being semicontinuous and thus promoting population mixing.

Energetic Particles Observed in the CUSP Region During a Storm Recovery Phase - S. Y. Fu; Q. G. Zong; Z. Y. Pu; C. J. Xiao; A. Korth; P. Daly; H. Reme (Surveys in Geophysics, 2005)

Multiple Flux Rope Events at the High-Latitude Magnetopause: Cluster/Rapid Observation on 26 January, 2001 - Z. Y. Pu; Q. -G. Zong; T. A. Fritz; C. J. Xiao; Z. Y. Huang; S. Y. Fu; Q. Q. Shi; M. W. Dunlop; K. -H. Glassmeier; A. Balogh; P. Daly; H. Reme; et al. (Surveys in Geophysics, 2005)

Amazonian climate: results and future research - J. H. C. Gash; C. Huntingford; J. A. Marengo; R. A. Betts; P. M. Cox; G. Fisch; R. Fu; A. W. Gandu; P. P. Harris; L. A. T. Machado; C. von Randow; M. A. Silva Dias (Theoretical and Applied Climatology, 2004)

Adult-Plant Resistance to Powdery Mildew in Knox 62 Wheat - J. W. Johnson; Yong-fu Ge; J. J. Roberts; P. Raymer; Yong Seo (Cereal Research Communications, 2003)

Trabecular Shear Stresses Predict In Vivo Linear Microcrack Density but not Diffuse Damage in Human Vertebral Cancellous Bone - Yener N. Yeni; Fu J. Hou; Traci Ciarelli; Deepak Vashishth; David P. Fyhrie (Annals of Biomedical Engineering, 2003)

Attenuated Lapinized Chinese Strain of Classical Swine Fever Virus: Complete Nucleotide Sequence and Character of 3′-Noncoding Region - H. X. Wu; J. F. Wang; C. Y. Zhang; L. Z. Fu; Z. S. Pan; N. Wang; P. W. Zhang; W. G. Zhao (Virus Genes, 2001)

Comparative study of platinum‐group elements in the Coto and Acoje blocks of the Zambales Ophiolite Complex, Philippines - Mei‐Fu Zhou; Graciano P. Yumul; John Malpas; Min Sun (Island Arc, 2000)
The Zambales Ophiolite Complex (ZOC), Philippines, includes two geochemically distinct, ophiolitic assemblages: the high‐Al chromitite‐bearing Coto Block and high‐Cr chromitite‐bearing Acoje Block. This paper reports a comparative platinum‐group element (PGE) study of these two blocks. The PGE data were obtained using Ni‐sulfide fire assay preconcentration combined with inductively coupled plasma mass spectrometry (ICP‐MS) measurement. Podiform chromitites in the Acoje Block have higher Cu, Ir, Ru and Rh contents than their equivalents in the Coto Block, although chromitites from both have similar Pt and Pd contents. The PGE mantle‐normalized patterns of dunites from the two blocks are also different: dunites from the Coto Block are depleted in Pt, whereas those from the Acoje Block have a relatively flat pattern. The data demonstrate that Coto and Acoje Blocks have different origins in terms of their source region and partial melting processes. This study implies that the ZOC is a paired ophiolite belt formed in an island arc and back‐arc basin environment.

Comparative study of platinum-group elements in the Coto and Acoje blocks of the Zambales Ophiolite Complex, Philippines - Mei-Fu Zhou; Graciano P. Yumul; John Malpas; Min Sun (Island Arc, 2000)

Erratum: “Short Term In Vivo Precision of Proximal Femoral Finite Element Modeling” (Ann. Biomed. Eng. 28:408–414, 2000) - Dianna D. Cody; Fu J. Hou; George W. Divine; David P. Fyhrie (Annals of Biomedical Engineering, 2000)

Transgenic rice as a system to study the stability of transgene expression: multiple heterologous transgenes show similar behaviour in diverse genetic backgrounds - D. Gahakwa; S. B. Maqbool; X. Fu; D. Sudhakar; P. Christou; A. Kohli (Theoretical and Applied Genetics, 2000)

Short Term In Vivo Precision of Proximal Femoral Finite Element Modeling - Dianna D. Cody; Fu J. Hou; George W. Divine; David P. Fyhrie (Annals of Biomedical Engineering, 2000)

The barriers to bluetongue virus infection, dissemination and transmission in the vector, Culicoides variipennis (Diptera: Ceratopogonidae) - H. Fu; C. J. Leake; P. P. C. Mertens; P. S. Mellor (Archives of Virology, 1999)

Three-dimensional organization and dynamic changes of the actin cytoskeleton in embryo sacs ofZea mays andTorenia fournieri - B. -Q. Huang; Y. Fu; S. Y. Zee; P. K. Hepler (Protoplasma, 1999)

Degradation of 3-phenylpropionic acid by Haloferax sp. D1227 - W. Fu; P. Oriel (Extremophiles, 1999)

Gentisate 1,2-dioxygenase from Haloferax sp. D1227 - W. Fu; P. Oriel (Extremophiles, 1998)

Expression and Immunolocalisation of the Snowdrop Lectin, GNA in Transgenic Rice Plants - Duraialagaraja Sudhakar; Xiangdong Fu; Eva Stoger; Sarah Williams; Jacqui Spence; David P. Brown; Muthusamy Bharathi; John A. Gatehouse; Paul Christou (Transgenic Research, 1998)

Angiotensin II receptors: Localization of type I and type II in rat epididymides of different developmental stages - P. S. Leung; H. C. Chan; L. X. M. Fu; P. Y. Leung; S. B. C. Chew; P. Y. D. Wong (The Journal of Membrane Biology, 1997)

Case 23 nomination of precursory seismic quiescence as a significant precursor - Max Wyss; R. E. Habermann; P. Bodin; Carl Kisslinger; R. O. Burford; F. W. Klein; A. C. Johnson; Zhengxiang Fu (Pure and Applied Geophysics, 1997)

Stereoselective formation of a K-region dihydrodiol from phenanthrene by Streptomyces flavovirens - John B. Sutherland; James P. Freeman; Allison L. Selby; Peter P. Fu; Dwight W. Miller; Carl E. Cerniglia (Archives of Microbiology, 1990)